Analytical approach for modelling of thread crimp in jacquard woven two-dimensional fabrics - Brigita Kolcavová Sirková; Iva Mertová (Scientific Reports)
Abstract This study investigates and discusses the thread crimp in the jacquard woven two-dimensional (2D) fabrics. The study of thread crimp is important for technologists and weavers from a practical point of view, as it has a considerable influence on the behavior of the fabric during weaving on the weaving machine, and subsequently in the finishing process. The basis of the study is the creation of an analytical approach that allows estimating the thread crimp before weaving. The crimp of threads as well as waviness of yarn in a jacquard fabric is influenced by the complexity of the input image and the chosen weave combination. The thread transition parameter was introduced for prediction. The parameter responds both to changes in areas in the input image and to changes in the interlacing in the weave. An algorithm has been built in the ProTkaTex software that records the transition of both warp and weft threads in the pattern’s weave. The theoretical predicted values of thread crimp in jacquard fabrics were compared with experimentally obtained values. Two conclusions are evident from the results, the first is that the presented model is applicable for estimating crimp threads in jacquard fabric, and the introduced parameter of thread transitions in the jacquard fabric pattern can respond to pattern change. The results show that the crimp value of the threads increases with the increasing number of transitions. In this study, two methods are used for the experimental analysis of crimp threads in jacquard fabric. Finally, their advantages and disadvantages in relation to jacquard fabric are discussed.